Modulation of antioxidant defence system in brain of rainbow trout (Oncorhynchus mykiss) after chronic carbamazepine treatment - Li, Zhi-Hua; Zlabek, Vladimir; Velisek, Josef; Grabic, Roman; Machova, Jana; Randak, Tomas (Comparative biochemistry and physiology. Toxicology & pharmacology, 2010)
We investigated the effect of long-term exposure to CBZ on the antioxidant system in brain tissue of rainbow trout. Fish were exposed to sublethal concentrations of CBZ (1.0 microg/L, 0.2mg/L or 2.0mg/L) for 7, 21, and 42 days. Oxidative stress indices (LPO and CP) and activities of antioxidant enzymes (SOD, CAT, GPx and GR) in fish brain were measured. In addition, non-enzymatic antioxidant (GSH) was determined after 42 days exposure. Carbamazepine exposure at 0.2mg/L led to significant increases (p<0.05) of LPO and CP after 42 days and, at 2.0mg/L, after 21 days. Activities of the antioxidant enzymes SOD, CAT, and GPx in CBZ-treated groups slightly increased during the first period (7 days). However, activities of all measured antioxidant enzymes were significantly inhibited (p<0.05) at 0.2mg/L exposure after 42 days and after 21 days at 2.0mg/L. After 42 days, the content of GSH in fish brain was significantly lower (p<0.05) in groups exposed to CBZ at 0.2mg/L and 2.0mg/L than in other groups. Prolonged exposure to CBZ resulted in excess reactive oxygen species formation, finally resulting in oxidative damage to lipids and proteins and inhibited antioxidant capacities in fish brain. In short, a low level of oxidative stress could induce the adaptive responses of antioxidant enzymes, but long-term exposure to CBZ could lead to serious oxidative damage in fish brain.
Keywords: Reactive Oxygen Species; karbonylace proteinů; Glutathione Reductase; časové faktory; Glutathione; glutathionreduktasa; katalasa; Antioxidants; Catalase; Brain; látky reagující s kyselinou thiobarbiturovou; Water Pollutants, Chemical; rybí proteiny; Superoxide Dismutase; glutathion; Animals; Dose-Response Relationship, Drug; Lipid Peroxidation; Oncorhynchus mykiss; karbamazepin; antioxidancia; Fish Proteins; zvířata; Glutathione Peroxidase; Time Factors; peroxidace lipidů; Protein Carbonylation; mozek; reaktivní formy kyslíku; Thiobarbituric Acid Reactive Substances; superoxiddismutasa; Oxidative Stress; oxidační stres; vztah mezi dávkou a účinkem léčiva; chemické látky znečišťující vodu; Carbamazepine; glutathionperoxidasa